Electrodialytic Removal of Cadmium from Brackish Water: Effects of Operating Parameters - Ali, Mourad Sik; Hafiane, Amor; Dhahbi, Mahmoud; Hamrouni, Béchir (Journal of Membrane and Separation Technology, 2014)
The continuous increase of environmental regulations make interesting to find effective and efficient methods for processing effluents containing metal ions. This research focuses on cadmium removal from brackish water by an electro-membrane process: The electrodialysis. Experiments were carried out on synthetic brackish water solutions and using a laboratory scale electrodialysis system. The influence of several parameters on process efficiency was investigated. The efficiency of this process was assessed by the determination of five parameters: The demineralization rate, the removal rate and the transport flux of cadmium, the current efficiency and the specific power consumption. The applied voltage, the feed flow rate, the pH and cadmium initial concentration of the feed solution have a significant effect on the process efficiency and mainly on the cadmium transfer from dilute to concentrate compartment. In contrast, feed ionic strength seems to affect only the SPC and not the R(Cd).